2020
DOI: 10.1186/s40623-020-01170-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SuperDARN peak electron density estimates based on elevation angle measurements to ionosonde and incoherent scatter radar measurements

Abstract: Measurements of the electron density at the F region peak by the Canadian Advanced Digital Ionosonde (CADI) and the Resolute Incoherent Scatter Radar (RISR) are used to assess the quality of peak electron density estimates made from elevation angle measurements by the Super Dual Auroral Radar Network (SuperDARN) high-frequency radar at Rankin Inlet (RKN). All three instruments monitor the ionosphere near Resolute Bay. The CADI-RKN joint dataset comprises measurements between 2008 and 2017 while RISR-RKN datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…One is the Digisonde that detects signals from localized regions with the strongest electron density, while the SuperDARN ZHS radar range gate, with a spatial resolution of 45 km, could smooth out the peak electron densities. This smoothing effect is expected to be stronger for ionospheric conditions with higher patchiness and poorer propagation conditions (Koustov et al., 2020). Second, the critical frequency is manually acquired from Digisonde ionograms containing the extraordinary wave, which has a higher frequency than the ordinary wave, that is, O‐mode wave, by half the electron gyrofrequency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One is the Digisonde that detects signals from localized regions with the strongest electron density, while the SuperDARN ZHS radar range gate, with a spatial resolution of 45 km, could smooth out the peak electron densities. This smoothing effect is expected to be stronger for ionospheric conditions with higher patchiness and poorer propagation conditions (Koustov et al., 2020). Second, the critical frequency is manually acquired from Digisonde ionograms containing the extraordinary wave, which has a higher frequency than the ordinary wave, that is, O‐mode wave, by half the electron gyrofrequency.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the quality of the peak electron density estimates made from elevation angle measurements by the SuperDARN Rankin Inlet (RKN) radar was recently carried out by Koustov et al. (2020). By comparing the SuperDARN RKN results to ionosonde and incoherent scatter radar measurements, the underestimation of peak electron density by SuperDARN radar (by up to 30% in their cases) could be mainly due to low background electron densities (Koustov et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work of comparison of SuperDARN peak electron density estimates with measurements from the ionosonde and the incoherent scatter radar in Canada from 2008 to 2017, Koustov et al (2020) concluded that the SuperDARN electron density estimates are a valuable resource for their use in statistical studies, such as those focused on seasonal and solar cycle effects.…”
Section: Superdarnmentioning
confidence: 99%